2022
DOI: 10.3390/polym14183793
|View full text |Cite
|
Sign up to set email alerts
|

Functional Polymer and Packaging Technology for Bakery Products

Abstract: Polymeric materials including plastic and paper are commonly used as packaging for bakery products. The incorporation of active substances produces functional polymers that can effectively retain the quality and safety of packaged products. Polymeric materials can be used to produce a variety of package forms such as film, tray, pouch, rigid container and multilayer film. This review summarizes recent findings and developments of functional polymeric packaging for bakery products. Functional polymerics are mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…A wide variety of materials is used as packaging. Recent developments in packaging technology include the evolution of active and smart packaging, where active antioxidant, antimicrobial, flavoring, and oxygen-scavenging agents are added to supplement the desired packaging characteristics and enhance shelf life [ 8 , 9 , 10 , 11 , 12 , 13 ]. However, increasing concerns have been expressed about the use of fossil-based plastic packages for food coverings, which negatively impact the environment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of materials is used as packaging. Recent developments in packaging technology include the evolution of active and smart packaging, where active antioxidant, antimicrobial, flavoring, and oxygen-scavenging agents are added to supplement the desired packaging characteristics and enhance shelf life [ 8 , 9 , 10 , 11 , 12 , 13 ]. However, increasing concerns have been expressed about the use of fossil-based plastic packages for food coverings, which negatively impact the environment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The essential oils make the biopolymeric films active, while other properties of such films, such as mechanical, barrier, or opacity properties, should also be acceptable. These features of essential oils contributed to their use in packaging for seafood products to prevent spoilage [ 76 ], for bakery products against mold and yeast [ 77 ], and for meat products to protect from lipid and protein oxidation and microorganism growth [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study by Photisarattana et al [ 72 ] also revealed that packaging pork meat with films containing ZnO could reduce microbial growth and lipid oxidation, extending the shelf-life of pork meat samples. Moreover, recent studies have proposed that the addition of active substances produces functional active packaging, which preserves several quality changes and microbial growth in food products, replacing the direct addition of preservatives into foods [ 73 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%